PENGGUNAAN BAHAN TAMBAHAN PANGAN OLEH PARA PEDAGANG JAJANAN DI SEKOLAH DASAR KECAMATAN PADANG UTARA - Siska Komala Sari; Anni Faridah; Rahmi Holinesti (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2018)
The purpose of research was to describe the use of food additives by the vendors of street food in North Padang District Elementary School. This type of research is quantitative descriptive. The study population was street food vendors in the neighborhood elementary school in the district of Padang Utara totaling 53 traders, sampling using total sampling technique. Collecting data using a questionnaire and analyzed using a percentage formula. Data collecting by questioner and analysys by percentace. The results of the study as follows: 1) Type of Food Additives dyes used synthetic red, yellow, green and brown. Synthetic sweeteners are used, sakarine. MSG flavor and aroma boosters, preservatives are rarely used. Natural food additives used natural dyes, dye green from pandan leaves and leaf suji, the yellow color of turmeric. Natural sweetener from cane sugar, brown sugar, honey, natural preservatives garlic, sugar, salt, flavor and aroma of garlic, pepper, and lime leaves. (2) The dose BTP used by traders snacks, BTP synthetic dyes above the maximum limit of 500 mg/kg, a sweetener within the limits of a maximum of 300 mg/kg, a flavor enhancer MSG above the maximum limit of 300 mg/kg, adders aroma vanilie above the maximum limit of 0.9/kg and (3) Knowledge of Food Additives are used by traders snacks including unfavorable categoryKata kunci: Food Additives, Food Snacks, snacks Traders